Design, synthesis and antibacterial activity of a class of novel molecular engineering analogues of Tachyplesin I. (December 2022) - Zhang, Chuanliang; Gao, Jiangming; Yang, Xianmin; Song, Shengnan; Huang, Dingmin; Wang, Zhenwei; Sun, Haotian; Liu, Hao; Su, Xianbin
Abstract: Tachyplesin I (TP-I) is a marine-derived antimicrobial peptide isolated from the hemocyte membrane of Japanese horseshoe crab ( Tachypleus tridentatus ) with broad antimicrobial spectrum. It consists of 17 amino acid residues and shows a characteristic structure with three tandem repeats of a tetrapeptide sequence. The three tandem repeats of a tetrapeptide sequence are the key components of the amphipathic β-hairpin structure of TP-I and we proposed that these fragments were critical for the antimicrobial activity, and designed a class of novel molecular engineering analogs of TP-I via re-combination of the three tetrapeptide fragments with different numbers of disulfide bonds in a search of therapeutically valuable lead compound. The synthesis of cyclic peptides with 1/2 disulfide bond(s) are challenging and we successfully prepared most of them using the orthogonal Cys protection strategy. The antimicrobial assay result revealed that the molecular engineering analogs of TP-I via fragment re-combination with 2 disulfide bonds maintained the antimicrobial potency across the range of microbes and confirmed the importance of tetrapeptide fragments and disulfide bonds. Of particular interest, analogue TP-I-R2 exhibited good antimicrobial activity against most of the tested microbes with MIC ranging from 4 to 128 μg/mL. Moreover, TP-I-R1, TP-I-R1b and TP-I-R3 particularly exhibited higher potency of more than 16/16/8-fold against Grampositive Bacillus pumilus strains than TP-I, TP-I-R2 and TP-I-R4 showed comparable potency against Gramnegtive Salmonella typhimurium strains with TP-I. These compounds may be considered as promising lead for further development toward new treatments for infections caused by multiple bacterial pathogens. Graphical Abstract: ga1 Highlights: A class of novel molecular engineering analogues of Tachyplesin I (TP-I) were designed and synthesized. TP-I-R2 exhibited broader antimicrobial spectrum and good antimicrobial potency. TP-I-R2 could be considered as promising lead for the dicovery of novel antibiotics.